Walter Brendel and the dawn of transplantation research in Germany - Land, Walter G. (Frontiers in Transplantation, 2024)
Walter Brendel was a physiologist who headed the Institut of Experimental Surgery at the University of Munich (LMU) from 1961 until 1989. His legendary career began with the development of an anti-human lymphocyte globulin (ALG) at his Institute during the late 1960s. The initial successful treatment of a small number of patients culminated in the co-treatment of the first successfully heart-transplanted patient in Capetown, South Africa (successful reversal with ALG of an acute allograft rejection). Walter Brendel was a pioneering personality whose work has laid a wide platform for the promotion of interdisciplinarily conducted innovative research programs in various domains of translational science and medicine. Among the many innovative achievements, the most notable are: discovery of involvement of the alternative pathway of complement activation in hyperacute xenograft rejection; induction of immunological tolerance to horse IgG as a means to prevent anaphylactic reactions during ALG therapy; development and clinical implementation of the extracorporeal shock wave lithotripsy for extracorporeal destruction of renal and ureteral calculi. The legacy of Brendel continues with the foundation of the Walter-Brendel Kolleg für Transplantationsmedizin (i.e., the German Transplant School for Transplantation Medicine), which has been held annually since 1994.